Modelling pellet size and shape evolution during the breakage stage in spheronisation - Whelan-Smith, J.; How, M. S.; Rough, S. L.; Wang, L.; Wilson, D. I. (Elsevier BV, 2024)
In the breakage stage of extrusion-spheronisation, initially cylindrical extrudates undergo simultaneous breakage and rounding on a rotating friction plate. This sets the starting conditions (number of pellets, size and shape distributions) for the subsequent, lengthy, rounding stage. The simultaneous evolution of pellet size and shape during the initial stages of spheronisation has not been considered in depth. Wang et al. (2021) AIChEJ, 67(6), e17247 investigated the breakage of 2 mm diameter microcrystalline cellulose/water extrudates and modelled the evolution of length using a 1-D population balance model. Here the data (over 17,000 images) were reanalysed and classified by both length and shape (8 shape classes). Their model was extended to 2-D (tracking size and shape), and the data fitted by a combination of optimization approaches. The effect of pellet length on the likelihood of breakage over rounding, and the influence of plate rotation speed and initial number of extrudates, is reported.